(untitled) (Research, Society and Development, 2021)
This article is to address perspectives related to entrepreneurship and innovation and what are the types of companies and their differentiations, as well as the difficulties encountered by them to exist and to deal more deeply with the difficulties of a STARTUP, a point that will culminate in the demonstration of the advantages of the Single-Member Limited Liability Company, and why this is the most appropriate choice in the corporate regime of this company that has the idea of being innovative. Guiding the objective of this work, the present study used literatures, doctrines and laws that deal with the theme raised, where authors show definitions and procedures that must be adopted in the corporate type, thus clarifying the understanding that one has in this business sphere. Based on the study developed, it was observed that the Single-Member Limited Liability Company - SLU, by having specificities and differentiated rules, becomes less bureaucratic and therefore less costly, consequently providing an opportunity for better evolution and growth of the entrepreneur in the labor market.